Flexural behaviour of polyethylene terephthalate (PET) fibre in concrete - Kuah, Yi Mei (2015)
Today there are still many issues about landfill capacity problem. The global has the same mission in reducing the land capacity of world. Plastic waste is 24% over 17,000 of total municipal waste in Malaysia. Plastic waste has a slow degradation rate. This means that plastic waste is a compound which is hard to decompose in landfill. Polyethylene terephthalate (PET) is one type of plastic which is made by virgin plastic usually used to packaging of drink. According to Lesley McFadzean the decompose rate of a plastic bottle is 450 years. These mean that PET will occupy the landfill capacity with 450 year. In this development generation, plastic bottle still used widely and is a life essential for human. There are many countries had tried to reduce the number of PET, such as China created bottle-recycling vending machines and United State form National Association for PET Container Resources (NAPCOR) to reduce the PET’s waste. They are finding an alternative ways to reduce PET in landfill capacity. Using PET in construction material is not fresh in the global. In Japan they use PET to spraying and lining of tunnels. In this study PET is used as fibre to investigate the flexural behaviour of concrete. The objectives of this study are: (a) to determine the flexural strength of concrete which have addition of PET strip (b) to determine the performance of different length of PET strip in concrete (c) Compare the flexural strength of conventional and addition of PET strips concrete. The PET is hand cut into 10mm width and 20 mm, 40 mm and 60 mm length. The slump test, flexural test and compression test were carried out to indicate the performance of concrete. The results show that the increase in length of PET fibre the: (a) compressive strength increase (b) flexural strength increase (c) crack width control improved (d) ductility of concrete increase